AJCC 8th Edition oral cavity squamous cell carcinoma staging – Is it an improvement on the AJCC 7th Edition?. (July 2018) - Pollaers, Katherine; Hinton-Bayre, Anton; Friedland, Peter L.; Farah, Camile S.
Highlights: AJCC 8th Edition Oral Cavity Cancer staging includes depth of invasion and extracapsular extension. AJCC 7th and 8th Editions discriminated between stages for overall survival. AJCC 8th Edition discriminated between overall stages and T category for disease free survival. Abstract: Objectives: To explore the prognostic and discriminatory ability of the AJCC 8th Edition Oral Cavity cancer staging in a non-North American population, and compare it to the previously used AJCC 7th Edition. Materials and methods: Retrospective chart review was performed at a tertiary referral Otolaryngology, Head Neck and Skull Base Department in Australia, from June 2002 to June 2017. Oral cavity squamous cell carcinoma cases were staged according to AJCC 8th Edition, which was compared to AJCC 7th Edition staging, for disease-free survival (DFS) and overall survival (OS). DFS and OS were analysed using Kaplan-Meier curves. Results: There were 118 patients treated for OSCC, with an average age of 61 years, 63% were male. Overall survival grouped by stage demonstrated statistically significant discrimination between cancer stages using both the AJCC 7th and AJCC 8th Editions. AJCC 7th Edition did not discriminate between stages for DFS. Conversely, AJCC 8th Edition did statistically significantly discriminate for DFS (p = 0.0002). The DFS for both Stage 4a and 4b was significantly worse than cases in Stage 1. AJCC 8th Edition T stage was statistically significantly related to DFS (p = 0.0199), while the AJCC 7th Edition T stage was not. Conclusion: The AJCC Cancer Staging Manual 8th Edition includes both the depth of primary tumour invasion and extracapsular extension of lymph node metastases. The AJCC 8th Edition OSCC staging system showed improved disease-free survival discrimination between overall stages and between T categories, while AJCC 7th Edition did not.